Monthly Logistics Planning for a Trading Company - ÜLKÜ, İLAYDA; KULLAB, HUTHAYFAH; AL MULQI, TALHA; ALMSADI, ALI; ABOUSALEH, RAED (Digitizing Production Systems, ISPR 2021, 2022)
In this study, the transportation problem is considered in order to minimize the total traveling distance between the nodes. The nodes represent the hospitals and the warehouse. The data is obtained by Salem Trading Company (STC) that operates in various medical sectors including Urology, Gynecology, Endoscopy, Surgery, and other operations. STC has two types of vehicles; the big vehicle and the small vehicle. The big vehicle is used for the machines and it contains up to 4 machines. Whereas, the small vehicle is used for delivering the masks and gloves and its capacity is up to 200 boxes. In order to serve all the market need, they currently have a traditional logistics plan to ship products from the main warehouse to the Hospitals located in Qatar. In this study, there are two stages proposed to solve the transportation problem. In the first stage, the assignment problem is used to determine the unused capacity of each vehicle used. Then, the output of the first stage is used as an input in the second stage in order to apply the Vehicle Routing Problem (VRP). With this second stage, the optimal routes are obtained with the minimum cost. Firstly, the required data will be obtained from the company, which include the number of hospitals, the demand of each hospital, the capacity of the vehicles, the distance between hospitals and the warehouse, loading and unloading time of the vehicle, and the volume of the products. This study focus on finding the low-cost weekly logistics plan for hospitals in Qatar. Two mathematical models are developed to solve the problem with GAMS software. As a result, by using the assignment and VRP model, the unused capacity is increased from 38 to 18 and reduce the cost from 2470 TL to 1170 TL as in Qatar the cost of the fuel is not high, also on the time restriction is focused.
21st International Symposium on Production Research (ISPR) - Digitizing Production System
Part of the book series: Lecture Notes in Mechanical Engineering ((LNME)).
Keywords: Vehicle Routing